Analiza wsparcia oczekiwanego z ustaleniem jego dawców w odniesieniu do osób z wyłonioną stomią jelitową = Expected and received support as well as its providers at patients with emerged intestinal stoma - Zdzisława Cecylia Szadowska-Szlachetka; Marzena Janczaruk; Jadwiga Kijewska; Elżbieta Starosławska; Marta Łuczyk (Kazimierz Wielki University, 2015)
Szadowska-Szlachetka Zdzisława, Janczaruk Marzena, Kijewska Jadwiga, Starosławska Elżbieta, Łuczyk Marta. Analiza wsparcia oczekiwanego z ustaleniem jego dawców w odniesieniu do osób z wyłonioną stomią jelitową = Expected and received support as well as its providers at patients with emerged intestinal stoma. Journal of Education, Health and Sport. 2015;5(3):91-102. ISSN 2391-8306. DOI: 10.5281/zenodo.16253 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%283%29%3A91-102 https://pbn.nauka.gov.pl/works/548060 http://dx.doi.org/10.5281/zenodo.16253 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.01.2014. Revised 27.02.2015. Accepted: 12.03.2015.   Analiza wsparcia oczekiwanego z ustaleniem jego dawców w odniesieniu do osób z wyłonioną stomią jelitową Expected and received support as well as its providers at patients with emerged intestinal stoma   Zdzisława Szadowska-Szlachetka1, Marzena Janczaruk2, Jadwiga Kijewska2, Elżbieta Starosławska2, Marta Łuczyk1   1Uniwersytet Medyczny w Lublinie, Katedra Onkologii i Środowiskowej Opieki Zdrowotnej 2Centrum Onkologii Ziemi Lubelskiej im. św.Jana z Dukli   Streszczenie Wstęp Wyłonienie stomii jelitowej jest to sytuacja bardzo trudna w której występuje naruszenie integralności fizycznej człowieka. Osoby, u których w trakcie zabiegu została wyłoniona stomia jelitowa czują się bezradne, zagubione i okaleczone. Postrzegają ją jak coś nienaturalnego, obcego dla nich [1]  Pojawia się obawa dotycząca procesu adaptacji do zmian, jakie zachodzą w ciele człowieka oraz do nowej sytuacji życiowej. Ważne jest przygotowanie pacjenta do zmienionej sytuacji życiowej poprzez udzielenie mu wsparcia emocjonalnego, informacyjnego, instrumentalnego, duchowego zarówno przez pracowników służby zdrowia, psychologa, osobę duchowną oraz przez bliskich chorego. Cel: Celem pracy było ustalenie zapotrzebowania na różne rodzaje wsparcia oraz ustalenie jakie są oczekiwania pacjentów z wyłonioną stomią jelitową co do osób, świadczących im wsparcie. Materiał i metoda Badani to 102 osoby leczone w Centrum Onkologii Ziemi Lubelskiej. W pracy zastosowano metodę sondażu diagnostycznego z wykorzystaniem techniki wywiadu. Narzędziem był autorski kwestionariusz ankiety. Wyniki Respondenci  potrzebowali  najczęściej  wsparcia emocjonalnego, informacyjnego i duchowego,  rzadziej instrumentalnego  oraz materialnego. Wnioski 1)                   Pacjenci z wyłonioną stomią jelitową potrzebują wsparcia informacyjnego i emocjonalnego. 2)                   Niewielki odsetek pacjentów potrzebuje wsparcia materialnego, duchowego i instrumentalnego. 3)                   Kobiety z wyłonioną stomią jelitową  oczekują najczęściej wsparcia emocjonalnego i duchowego.   Summary Introduction Emergence of intestinal stoma is a very difficult situation involving violation of a physical integrity of human. People in which, during the operation, the intestinal stoma has been emerged, feel helpless, confused and mutilated. They perceive it as something unnatural,  strange [1]  There is a concern about the process of adaptation to changes that occur in the human body and to the new life situation. It is important to prepare a patient for the changed life situation by providing him/her emotional, information, instrumental, spiritual support by health care workers, psychologists, spiritual person and by the person's family and friends. Purpose: The purpose of the study was to determine the demand for different types of support and to determine what are the expectations of patients with emerged intestinal stoma for people providing them with support. Material and method Respondents are 102 people treated in St Johns' Oncology Center in Lublin (COZL). The study used diagnostic survey method using interview technique. Author's survey questionnaire was used as a tool. Results Respondents most frequently needed emotional, information and spiritual support,  less frequently instrumental and material support. Conclusions 1)                   Patients with emerged intestinal stoma need information and emotional support. 2)                   Small percentage of patients needs material, spiritual and instrumental support. 3)                   Women with emerged intestinal stoma most frequently expect emotional and spiritual support.   Key words: intestinal stoma, support provided to a patient, demand.   Słowa kluczowe: Stomia jelitowa, wsparcie pacjenta , zapotrzebowanie.